2018
DOI: 10.5194/cp-14-339-2018
|View full text |Cite
|
Sign up to set email alerts
|

Variations in Mediterranean–Atlantic exchange across the late Pliocene climate transition

Abstract: Abstract. Mediterranean-Atlantic exchange through the Strait of Gibraltar plays a significant role in the global oceanclimate dynamics in two ways. On one side, the injection of the saline and warm Mediterranean Outflow Water (MOW) contributes to North Atlantic deep-water formation. In return, the Atlantic inflow is considered a sink of less saline water for the North Atlantic Ocean. However, while the history of MOW is the focus of numerous studies, the Pliocene Atlantic inflow has received little attention s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 76 publications
(116 reference statements)
0
2
0
Order By: Relevance
“…Previously, studies have concluded that the Atlantic Ocean is a source of contamination to the Mediterranean Sea or that there is no significant flow of PFAAs between the water bodies . These conclusions were based on comparisons of surface water measurements made in different studies in the Mediterranean Sea , and the Atlantic Ocean. ,, However, since outward transport of Mediterranean seawater into the Atlantic Ocean occurs at intermediate depth (500–1500 m) as well as at the surface, comparisons of surface water measurements alone are not suitable to determine the flux of PFAAs between the two water bodies.…”
Section: Resultsmentioning
confidence: 99%
“…Previously, studies have concluded that the Atlantic Ocean is a source of contamination to the Mediterranean Sea or that there is no significant flow of PFAAs between the water bodies . These conclusions were based on comparisons of surface water measurements made in different studies in the Mediterranean Sea , and the Atlantic Ocean. ,, However, since outward transport of Mediterranean seawater into the Atlantic Ocean occurs at intermediate depth (500–1500 m) as well as at the surface, comparisons of surface water measurements alone are not suitable to determine the flux of PFAAs between the two water bodies.…”
Section: Resultsmentioning
confidence: 99%
“…Such community diversity would be decisive to guarantee its migrations under climatic changes: richness of herbaceous life forms (Tomiolo and Ward 2018), ability for propagule fast migrations (Matlack 1994), or because of their biological capacities to colonize alpine environments (Alexander et al 2015). In this sense, the genetic flux involved along such glacial-interglacial processes (García-Gallardo et al 2018;Suc et al 2018) caused remarkable changes in the vegetation.…”
Section: Discussionmentioning
confidence: 99%